Recent research trends in quantum therapy: A scoping review - Si, Euna; Choi, Eun-Nyeo; Kim, Jeongseon; Cho, Sumi; Sung, Youngsil; Cheong, Hyeran; Seo, Seok-Hae; Jeon, Chanju; Lee, Wondeok (Edelweiss Applied Science and Technology, 2025)
This study aims to identify current research trends in quantum therapy across non-technical scientific domains, with a focus on providing future research directions. Utilizing Arksey and O’Malley’s five-stage scoping review framework, a systematic search was conducted in PubMed, Medline, and CINAHL for peer-reviewed studies published between 2020 and 2024. A total of 21 studies met the inclusion criteria. The analysis revealed a steady increase in quantum therapy research, predominantly in the form of review or descriptive studies. These were primarily concentrated in the fields of biology, chemistry, alternative and complementary medicine, and pharmacology, with only one study involving human participants. Findings indicate that the concept of quantum therapy remains inconsistently defined, and empirical clinical validation is significantly lacking. The study highlights the need for a unified theoretical framework, standardized methodologies, and interdisciplinary collaboration to enhance scientific rigor and applicability in clinical contexts. This review contributes by offering a foundational overview of quantum therapy research and emphasizes the importance of developing operational definitions and conducting human-centered clinical trials to realize the potential of quantum-based treatments in modern healthcare.